2020
DOI: 10.4314/sajas.v49i6.19
|View full text |Cite
|
Sign up to set email alerts
|

Influence of feeding systems on selected beef quality and sensory attributes

Abstract: Feeding systems and other factors associated with processing influence meat quality, and therefore sensory attributes. This study was conducted to assess the meat quality attributes of young grain-fed and older grass-fed steers that mostly affect consumer acceptability of beef. Eighty Bonsmara steers consisting of 20 each of A-age (0-tooth) grain-fed (AC) and grain-fed supplemented with zilpaterol (AZ), 20 each of grass-fed AB (1-2 teeth) and B-age (3 - 6 teeth) animals were used. This combination represented … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…This increased demand can be attributed to the perceived benefits that consumers believe grass-fed beef has in terms of sustainability and health [ 4 , 5 , 6 ]. Many studies have investigated the effects that grain and grass-feeding systems have on meat quality and found that grain-finished cattle tend to produce a more consistent product while meat from grass-fed animals tends to be more variable in sensory characteristics and shelf life [ 7 , 8 , 9 , 10 ]. For example, some studies reported that forage-fed beef had similar or greater sensory characteristics than grain-finished beef [ 11 , 12 ], while others reported grass-feeding to have negative impacts on quality [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…This increased demand can be attributed to the perceived benefits that consumers believe grass-fed beef has in terms of sustainability and health [ 4 , 5 , 6 ]. Many studies have investigated the effects that grain and grass-feeding systems have on meat quality and found that grain-finished cattle tend to produce a more consistent product while meat from grass-fed animals tends to be more variable in sensory characteristics and shelf life [ 7 , 8 , 9 , 10 ]. For example, some studies reported that forage-fed beef had similar or greater sensory characteristics than grain-finished beef [ 11 , 12 ], while others reported grass-feeding to have negative impacts on quality [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%